A delayed diagnosis of atypical immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome: A case report. Issue 12 (26th March 2021) - Zhang, Ying; Liu, Hanmin; Ai, Tao; Xia, Wanmin; Chen, Tingting; Zhang, Lei; Luo, Xiulan; Duan, Yaping
Abstract: Introduction: Immune dysregulation, polyendocrinopathy, enteropathy, and X-linked (IPEX) syndrome is a rare monogenic autoimmune disease, which is caused by mutations in the forkhead box protein 3 gene, can affect various systems. The typical clinical manifestations of IPEX are enteropathy, type 1 diabetes mellitus, and skin diseases. However, some atypical phenotypes can easily be misdiagnosed clinically. Patient concerns: A 9-year-and-7-month old patient suffered from recurrent wheezing, hematochezia, and eczematous dermatitis at the age of six months, but did not have any manifestations of autoimmune endocrinopathy. The patient was treated with glucocorticoids for more than six years, and he developed bronchiectasis. Diagnosis: Whole exome sequencing revealed a hemizygous pathogenic mutation c.1010G>A, p. (Arg337Gln) in Forkhead box protein 3 gene (NM_014009.3). Interventions: The patient was treated with oral mycophenolate mofetil combined with inhaled budesonide formoterol for six months after diagnosis. Outcomes: The respiratory symptoms of the patient seemed to be controlled but eczematous dermatitis progressed, which led the patient to give up the treatment. Conclusion: Early diagnosis and treatment of IPEX are crucial. Lung injury may be a major problem in the later stages of atypical IPEX, and mycophenolate mofetil seems to control the respiratory symptoms, but could induce significant skin side effects.